The Innovation Ultimatum: How six strategic technologies will reshape every business in the 2020s - Brown, Steve (Wiley, 2020)
Prepares leaders for the 2020s—an accessible guide to the key technologies that will reshape business in the coming decade Most businesses identify six key digital technologies—artificial intelligence (AI), distributed ledgers and blockchain, the Internet of Things (IoT), autonomous machines, virtual and augmented reality, and 5G communication—as critical to their relevance and growth over the coming ten years. These new disruptive technologies present significant opportunity for businesses in every industry. The first businesses to understand automation and these transformative technologies will be the ones to reap the greatest rewards in the marketplace. The Innovation Ultimatum helps leaders understand the key technologies poised to reshape business in the next decade and prepare their organizations for technology-enabled change. Using straightforward, jargon-free language, this important resource provides a set of strategic questions every leader will need to ask and answer in order to prepare for the impending changes to the business landscape. Author Steve Brown shares his insights to help leaders take full advantage of the next wave of digital transformation and describes compelling examples of how businesses are already embracing new technologies to optimize operations, create new value, and serve customers in new ways. Written for anyone that wants to understand how automation and new technology will fundamentally restructure business, this book enables readers to: * Understand the implications of technology-driven change across industrial sectors * Apply important insights to their own business * Gain competitive advantage by implementing new technologies * Prepare for the future of work and understand the skills needed to thrive in a post-automation economy * Adopt critical digital technologies in any organization Providing invaluable cutting-edge content, The Innovation Ultimatum is a much-needed source of guidance and inspiration for business leaders, board members, C-suite executives, and senior managers who need to prepare their businesses for the future.